26. Relationship between impulsivity traits and awareness of motor intention. Issue 12 (December 2016) - Giovannelli, F.; Mastrolorenzo, B.; Rossi, A.; Gavazzi, G.; Borgheresi, A.; Calistri, M.; Zaccara, G.; Viggiano, M.P.; Cincotta, M.
Abstract : Deficient voluntary control of behaviour and impulsivity are key aspects of impulse control disorders. The objective of the present study was to evaluate the relationship between behavioural measures of impulsivity and awareness of voluntary action. Seventy-four healthy volunteers completed the Barratt Impulsiveness Scale (BIS), a questionnaire used to measure impulsive personality traits, and a go/no-go task. Moreover, all participants performed a task in which, using the Libet's clock, they were requested to report the time of a self-initiated movement (M-judgment) or the time they first felt intention to move (W-judgment). A positive relationship between W-judgment and impulsivity measures emerged. Namely, high scores in the attentional and motor impulsivity subscales of BIS and in the number of inhibitory failure responses in the go/no-go task, were related to a low difference between the W-judgment and the actual movement (i.e. the awareness of intention to move was closer to the voluntary movement execution). In contrast no relationship emerged with M-judgment. Findings suggest that impulsivity may be related to a delayed awareness of voluntary action. We hypothesize that in impulse control disorders the interval between conscious intention and actual movement could be insufficient to allow a conscious 'veto' of the impending action.